Crack-free manufacture of single weld tracks on aluminum alloy 6013 with the usage of laser beam shaping and oscillation strategies - Thomas Stoll; Maximilian Schmitt; Laura-Marie Müller; Frank Palm (Journal of Advanced Joining Processes)
The present paper investigates the application of laser beam shaping and laser beam oscillations (wobbling) for laser processing of the crack-prone aluminum alloy 6013, used in automotive and aerospace applications. A comparison of different laser beam profiles, such as the commonly used Gaussian profile, a ring-core distribution with the intensity of 50 % in the ring and 50 % in the core, and a ring-shaped beam profile shows different cracking behavior of the material. The ring-shaped beam profile shows the most promising results due to a reduction of the thermal gradient G and an enhancement of the growth rate R, which isalso stated by the state of the art. A combination of laser beam shaping and laser beam oscillations shows reproducible crack-free processing of Al6013 sheets at all three beam profiles at different parameter combinations. The crack elimination can be attributed to the emergence of a more pronounced equiaxed grain structure in the fusion zone of the weld with the application of laser beam oscillations and laser beam shaping. Thus, the temperature gradient G, the growth rate R and, therefore, the cooling rate can be controlled with the presented variation of the laser beam shapes and scanning strategies. Furthermore, the penetration depth of the laser at a Gaussian beam profile can be reduced using laser beam shaping, showing shallower melt pools with a lower depth-to-width aspect ratio, also suitable for the process of powder bed fusion of metals using a laser-based system (PBF-LB/M).